The Relationship Between Paternal and Maternal Depression During the Perinatal Period: A Systematic Review and Meta-Analysis - Thiel, Freya; Pittelkow, Merle-Marie; Wittchen, Hans-Ulrich; Garthus-Niegel, Susan (Frontiers in Psychiatry, 2020)
Background: Meta-analyses suggest an increased prevalence of paternal depression during the perinatal period of around 10%. The relationship between paternal and maternal symptoms however, has received little attention. Objective: To determine pooled estimates pertaining to the relationship between paternal and maternal depression during the perinatal period according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. Data Sources: Studies reporting on the relationship between depression in fathers and mothers between the first trimester and the first year following childbirth were identified using PubMed, PsycINFO, and EMBASE for the period between November 2009 and February 2020. Study Selection: A total of 28 primary, empirical studies published in English or German, reporting effect estimates for the relationship of depression in mother-father/partner dyads, involving 11,593 couples, were included. Ten studies included multiple assessments, resulting in 64 extracted effects. Analysis: Information on correlations and odds ratios were extracted. Four random-effect analyses were conducted for the pooled association between paternal and maternal depression: (a) during the prenatal and (b) during the postnatal period, as well as for the prospective relationships between (c) paternal depression and maternal depression at a later timepoint, and (d) vice versa. Models were specified as restricted maximum-likelihood estimation. Heterogeneity was assessed using H2 and I2. Funnel plots, the Egger method, and the trim and fill test were used to assess publication bias. Sensitivity analyses with and without studies for which we approximated r were conducted. Data Synthesis: With substantial heterogeneity, positive associations were found between paternal and maternal depression (a) during pregnancy (r = 0.238), (b) in the postnatal period (r = 0.279), as well as for the prospective relationship between (c) paternal and later maternal depression (r = 0.192), and (d) maternal and later paternal depression (r = 0.208). Conclusion: Paternal depression showed positive correlations with maternal depression across the perinatal period. Given notable methodological and cultural heterogeneity and limitations of individual studies, it was not possible to further identify determining or moderating factors. Increasing evidence for implications of parental depression for child development warrants further scientific attention.